Die Entdeckung des Sterbens das menschliche Lebensende in beiden deutschen Staaten nach 1945 - Greiner, Florian 1981- (Quellen und Darstellungen zur Zeitgeschichte, 2023)
Since 1945, medical advancements and demographic change have fundamentally altered the end of life. Florian Greiner traces the different responses in East and West: the emergence of hospice movements and palliative medicine, the fight for assisted dying, and churches' search for religious meaning. His pioneering study starts with the experiences of World War II and ends with the reunified Federal Republic